2000
DOI: 10.1002/1097-4644(20001215)79:4<557::aid-jcb40>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells from osteoporotic patients produce a type I collagen-deficient extracellular matrix favoring adipogenic differentiation

Abstract: Mesenchymal stem cells (MSCs), precursor cells resident in the bone marrow, have the capacity to differentiate into bone, cartilage, fat, and connective tissue. We have recently reported that MSCs from "healthy" donors differ from cells obtained from osteoporotic postmenopausal women in their proliferation rate, mitogenic response to osteogenic growth factors, and potential to mineralize. The purpose of this study was to examine the factors that explain the differential capacity of MSCs derived from "healthy" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
121
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(132 citation statements)
references
References 36 publications
8
121
0
3
Order By: Relevance
“…Indeed, SPARC might act directly to influence cell fate in this example; conversely, the absence of SPARC might affect ECM assembly and/or localization of growth factors that in turn could influence differentiation. Rodriguez et al recently reported an analysis of the differentiative capacity of mesenchymal stem cells isolated from postmenopausal women with and without osteoporosis (20). Cells from osteoporotic patients produced less TGF-β and collagen I and exhibited an increased incidence of adipogenic differentiation in culture.…”
Section: Sparc and Differentiationmentioning
confidence: 99%
“…Indeed, SPARC might act directly to influence cell fate in this example; conversely, the absence of SPARC might affect ECM assembly and/or localization of growth factors that in turn could influence differentiation. Rodriguez et al recently reported an analysis of the differentiative capacity of mesenchymal stem cells isolated from postmenopausal women with and without osteoporosis (20). Cells from osteoporotic patients produced less TGF-β and collagen I and exhibited an increased incidence of adipogenic differentiation in culture.…”
Section: Sparc and Differentiationmentioning
confidence: 99%
“…During aging, the balance between bone formation and resorption shifts in favor of resorption, resulting in reduced bone mass and altered bone architecture. In vitro, bone marrow mesenchymal stem cells from patients with osteoporosis are more likely to differentiate into adipocytes than osteoblasts compared with cells isolated from patients with normal bone mass (1), and osteoporotic bones have increased accumulation of adipocytes in the trabecular bone marrow space (2)(3)(4)(5). These studies and data from mouse models of osteoporosis have prompted questions about whether increased bone marrow fat is a consequence or the cause of decreased bone mass in osteoporosis (6).…”
Section: Introductionmentioning
confidence: 99%
“…First, the self-renewal and proliferative ability of hBMSCs decreases due to aging [17][18][19] and diseases, such as osteoporosis and arthritis. 20,21 Second, the heterogeneity of adult stem cells from bone marrow indicates that only a very small proportion of cells can be considered stem cells and can differentiate into the osteogenic lineage. 22 In this regard, hESCs hold great promise.…”
mentioning
confidence: 99%